A biocultural examination of home food production and child growth in highland Peru. Issue 4 (27th May 2020) - Hoke, Morgan K.
Abstract: Objectives: Chronic malnutrition remains a persistent global health issue. This mixed methods investigation in rural Peru examines the role of home food production (HFP) in reducing child malnutrition by testing the following hypotheses: (a) higher HFP will be associated with higher infant z‐scores than those with less HFP and (b) infants with higher HFP will exhibit improved longitudinal growth outcomes across 6 months. Methods: Ethnographic methods include semi‐structured interviews and participant observation. A household survey and anthropometric data were collected twice, from 86 infants under of 24 months old. A HFP index (HFI) was generated based on reports of animals for meat consumption, eggs, milk, and agricultural products for home consumption. Kruskal‐Wallis tests were used to examine patterns of HFI and infant anthropometrics. Multivariate regressions were used to examine the relationships between HFP and infant height for age (HAZ), weight for age (WAZ), and triceps skinfold for age (TSAZ) in both rounds and 6‐month change between rounds (6MΔ). Results: There were no relationships between HFI and infant z‐scores in round one, however, HFI was significantly positively related to HAZ (B = 0.091, P  < .039) in round two and with 6MΔ in HAZ (B = 0.09, P  < .047). HFI did not predict WAZ or TSAZ in either round. Conclusions: HFP represents an important influence of infant growth in Nuñoa, likely through nutritional improvement due to increased availability of animal‐sourced foods and through contribution to household economy and maternal empowerment.